Buckling resistance of cold-formed thick-walled steel columns under combined axial compression and bending. (1st July 2022) - Zhou, Yi; Huang, Dongchuan; Li, Tianji; Li, Yinglei
Abstract: Cold-formed thick-walled steel structures are increasingly used in civil engineering in recent years. In this research, a fiber model analysis method is established to estimate the buckling resistance of cold-formed thick-walled steel columns and the accuracy of the fiber model is validated by the experimental data. By comparing to numerical results, accuracy of the existing design standards, including the European, American and Chinese standards, on predicting the capacity of columns under combined axial compression and bending is assessed. Appropriate column buckling curves are suggested for the European and Chinese standards. Then, new strength prediction formulae are proposed and this design method exhibits a higher accuracy than the current design standards. Finally, reliability analysis is conducted for the Chinese standard and the proposed design method. Optimal values for partial resistance factor and the design strength of Q235 and Q345 steel are suggested for the design of cold-formed thick-walled steel columns. Highlights: Fiber model for cold-formed thick-walled steel square columns. Suggestions for the most appropriate column buckling curves in design standards. Proposed design methods for columns under combined axial compression and bending. Reliability analysis to determine the design strength of steel.